Learning with the use of the internet - Borba, Marcelo C. [UNESP]; Clarkson, Philip; Gadanidis, George (Springer Nature, 2013)
In this chapter we discuss how the Internet is interacting with mathematics education. After briefly discussing the rise of the Internet and its impact on education, we suggest that it has the potential to disrupt mathematics teaching and learning. Moving far beyond its used as a data resource, we suggest the Internet will provide on-demand access to mathematics knowledge through the collaborative, multimodal and performative affordances of the media that it supports. We note that such affordances will not come to fruition until pedagogical practices have adapted to the rapid pace of this technological change. We conclude by noting that such fundamental change in the teaching of mathematics does have many obstacles, not least that approximately two-thirds of the world's population does not have sufficient access to the Internet-and in societies where access is available, access to the Internet often remains limited in classroom settings, particularly for students in low socio-economic areas.